Determination of reservoir properties through the use of computed X-ray microtomography – eolian sandstone examples - Dohnalik, Marek; Jarzyna, Jadwiga (Geology, Geophysics and Environment, 2016)
A possibility of examination of the rock pore structure by means of the X-ray computed microtomography was presented. Parameters characterizing the pore structure, i.e. porosity and coefficient of homogeneity of pore structure by local porosity examination and box counting dimension and mean chord length and normalized Euler number and coordination number were determined through pore structure image analyses. Complementary methods as pycnometry, mercury injection porosimetry and NMR were used to determine porosity and other factors to make the comparison and determine mutual relationships between petrophysical properties obtained from various sources.The study covered Rotliegend sandstones of eolian origin. Reservoir properties laboratory investigations were focused in three areas located in the marginal part of the eastern erg and middle part of the Polish Lowland Permian Basin. Rotliegend sediments in the study showed changeability in petrography and reservoir properties so the data were grouped into three parts according to geological regions. Computed X-ray microtomography gave differentiation of the investigated areas with respect to their pore structure and porosity development. This differentiation was confirmed by means of other applied laboratory methods.